Multifactor and multi-objective coupling design of hydrogen circulation pump - Zhai, Huanle; Li, Wei; Li, Jiwei; Shen, Chaoping; Ji, Leilei; Xu, Yuanfeng (Frontiers in Energy Research, 2024)
The hydrogen circulation pump (HCP) is an important power component of the hydrogen fuel system, used to recover the unconsumed hydrogen from the anode and transport it back to the inlet of the battery stack to improve the hydrogen utilization efficiency. In this paper, to determine the optimal parameter configuration of the HCP, a multifactor and multi-objective optimization design method is proposed, and the influences of various design parameters on the performance of the HCP are analyzed based on the verified overset grid simulation method. The research results show that the proposed coupling design method can effectively achieve the optimal parameter configuration of the HCP, with diameter-to-pitch ratio κ = 1.47, rotor blade number Z = 3, and helix angle φ = 60°, which is validated using another model with significant performance advantages. In the process of studying the influence of design parameters, it is found that the average flow rate of the HCP is directly proportional to the diameter-to-pitch ratio and the blade number, gradually decreases in the range of helix angle from 0° to 22.5°, and increases in the range of helix angle from 22.5° to 60°. The flow pulsation value and pressure pulsation value of the HCP are less affected by the diameter-to-pitch ratio, decrease with the increase of the blade number, and show a trend of first increasing and then decreasing with the increase of the helix angle.